Pengaruh Model Brain Based Learning (BBL) dan Regulasi Diri Terhadap Peningkatan Pemahaman Konsep Siswa Pada Materi Koloid - Siti Namiran Hadis; Muktiningsih Muktiningsih; Imam Santoso (Jurnal Riset Pendidikan Kimia (JRPK), 2017)
Chemical materials that are full of concepts and need to be understood by students one of them is colloidal material. Based on observations made in some schools found 70% of chemistry teachers argued that colloidal material has characteristic as above, but the students are less interested in learning, this resulted in understanding the concept is not optimal. Thus required learning model that maximizes the potential of the brain both cognitive and emotional aspects. One of the learnings that optimize brain potency is Brain-Based Learning (BBL). The primary purpose of this research is to get information about the influence of learning model (BBL and TGT) and self-regulation to understanding the concept of student colloid. The subjects of the study were public senior high school students in Tidore, with a total of 60 students in class XI. Based on the result of analysis with ANAVA 2 lane, showed that (1) colloid concept of student colloid is better if taught with BBL than TGT, (2) There is interaction between learning model and self regulation to understanding student concept, (3) high self regulation is better if taught with BBL, because students who have high self-regulation have the motivation and independence in solving the challenge, (4) While understanding the concept of students with low self-regulation is better if taught with TGT, Due to the presence of heterogeneous groups within TGT supports students who have low self-tregulation to collaborate with their group members so that understanding of conceptual understanding can occur well. Based on the result, it can be concluded that there is an influence of BBL model and self-regulation to understanding student concept. Keywords: Brain Based Learning, Team Games Tournamen, Self regulation, Understanding concept, Colloid.